دور مراجعي ديوان المحاسبة في الحد من ممارسات المحاسبة الإبداعية وتأثير ذلك على مصداقية التقارير المالية (Comprehensive Journal of Science, 2026)
The study aimed to examine the role of the external auditor in limiting creative accounting practices and the impact of this on the credibility of financial reports from the perspective of auditors of the Libyan Audit Bureau. To achieve this, the analytical descriptive method was used to obtain data and information related to the theoretical framework. The study population consisted of auditors from the Libyan Audit Bureau. A questionnaire was used as a tool to collect primary data related to the study topic. The data was processed and analyzed  using the SPSS statistical program, employing appropriate statistical tests and treatments to arrive at statistically significant results that support the study's subject.       The study concluded that auditors of the Libyan Audit Bureau apply procedures that limit the practice of creative accounting methods affecting financial statements. Furthermore, there are many modern trends and methods for detecting and limiting creative accounting practices, most notably corporate governance, audit committees, and the non-changing of accounting policies, among many other methods. The study also emphasized the need to enhance the efficiency of Audit Bureau auditors by establishing specialized training programs in this field to keep pace with potential developments.